2009
DOI: 10.1007/s11897-009-0012-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide regulation of autonomic function in heart failure

Abstract: Nitric oxide (NO) functions at all levels of the autonomic nervous system to influence sympathetic and parasympathetic control of cardiovascular function. It modulates the excitability of peripheral sensory and motor neurons of cardiovascular reflexes and of the central neurons that integrate their function. Its effects within this system are diverse and site specific, and at many levels, not well defined. Overall, however, most evidence suggests that the neuromodulator's influence acts to restrain sympathetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 62 publications
1
28
0
2
Order By: Relevance
“…Nitric oxide synthase is localized within intrinsic cardiac vagal neurons as well as stellate sympathetic ganglia. In parasympathetic neurons, NO serves to increase acetylcholine release via stimulation of soluble guanylate cylase [33,50], and direct modulation of vagal control of cardiac activity has been demonstrated [51] suggesting that NO modulation of parasympathetic activity may be important [34,52]. As described elsewhere in this issue, NO levels are known to be significantly altered in HF in complex patterns and could represent a significant component to vagal dysfunction in HF [34,53].…”
Section: Modulators Of Parasympathetic Functionmentioning
confidence: 90%
“…Nitric oxide synthase is localized within intrinsic cardiac vagal neurons as well as stellate sympathetic ganglia. In parasympathetic neurons, NO serves to increase acetylcholine release via stimulation of soluble guanylate cylase [33,50], and direct modulation of vagal control of cardiac activity has been demonstrated [51] suggesting that NO modulation of parasympathetic activity may be important [34,52]. As described elsewhere in this issue, NO levels are known to be significantly altered in HF in complex patterns and could represent a significant component to vagal dysfunction in HF [34,53].…”
Section: Modulators Of Parasympathetic Functionmentioning
confidence: 90%
“…e l s e v i e r . c o m / l o c a t e / y m v r e cardiovascular function at all levels of the autonomic regulation including central arterial baroreflex pathways (Schultz, 2009). However, no studies demonstrated arterial baroreflex feedback coupling with NO-mediated vasodilation which may have a particular clinical importance.…”
Section: Microvascular Researchmentioning
confidence: 99%
“…In central neurons, cGMP then can have diverse effects on neuronal excitability. Cyclic GMP can directly bind to and modulate cyclic nucleotide-gated ion channels, bind to phosphodiesterases to impair cAMP hydrolysis, or most prominently, activate cGMP-dependent protein kinase which can 180 directly or indirectly leads to phosphorylation of effector proteins or ion channels (Schultz, 2009). The effects of NO on baroreflex have been already demonstrated by several investigations.…”
Section: Nitric Oxide (No)mentioning
confidence: 98%
“…NO is a free radical synthesized from L-arginine by three isoforms of nitric oxide synthase (NOS): NOS1 (neural), NOS2 (inducible), and NOS3 (endothelial) and all three isoforms have been shown to influence autonomic neural function in some manner (Schultz, 2009). NO generated at nerve synapses diffuses in an autocrine and paracrine way to influence both presynaptic and postsynaptic events on excitatory and inhibitory synapses.…”
Section: Nitric Oxide (No)mentioning
confidence: 99%